Analisis Literatur : Peran Guru dalam Pembelajaran Tematik di SD - Suci Zuliani; Dea Mustika; Balqis Adelia; Febri Yollanda; Saskya Andini; Hadziqah Nadhira (STIKes Ibnu Sina Ajibarang, 2025)
Thematic learning at the elementary school level is designed to provide integrated and meaningful learning experiences, aligned with the thinking characteristics of young learners. The success of this approach is strongly influenced by the teacher’s role in designing, implementing, and evaluating the learning process. This study aims to examine in depth how teachers carry out their roles in thematic learning and identify the influencing factors. The research uses a literature review method by analyzing fifteen relevant sources, including academic journals and educational books. The findings show that teachers hold multifaceted roles as facilitators, motivators, instructional designers, and learning assessors. Teachers also play a crucial role in shaping students’ character through the integration of social values within thematic instruction. However, practical implementation still faces challenges such as limited time, administrative workload, and lack of professional training. The implications of this study emphasize the importance of strengthening teachers’ professional competence and institutional support to ensure thematic learning can be implemented effectively and sustainably in elementary schools.